2022
DOI: 10.2196/33754
|View full text |Cite
|
Sign up to set email alerts
|

Alignment Between Heart Rate Variability From Fitness Trackers and Perceived Stress: Perspectives From a Large-Scale In Situ Longitudinal Study of Information Workers

Abstract: Background Stress can have adverse effects on health and well-being. Informed by laboratory findings that heart rate variability (HRV) decreases in response to an induced stress response, recent efforts to monitor perceived stress in the wild have focused on HRV measured using wearable devices. However, it is not clear that the well-established association between perceived stress and HRV replicates in naturalistic settings without explicit stress inductions and research-grade sensors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 102 publications
3
10
0
Order By: Relevance
“…Future work should explore data collection of ECG in controlled conditions, potentially with an intervention (e.g., applying stressors in a lab) to evaluate the robustness of this data. This recommendation is also in line with Martinez et al conclusions that HRV may be best represented in controlled environments with specific stressors ( 25 ). While this would diminish the validity of ECG data to be used in real-life scenarios to identify stress, it could provide further clues as to how the relationship between these variables work and new directions of research.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Future work should explore data collection of ECG in controlled conditions, potentially with an intervention (e.g., applying stressors in a lab) to evaluate the robustness of this data. This recommendation is also in line with Martinez et al conclusions that HRV may be best represented in controlled environments with specific stressors ( 25 ). While this would diminish the validity of ECG data to be used in real-life scenarios to identify stress, it could provide further clues as to how the relationship between these variables work and new directions of research.…”
Section: Discussionsupporting
confidence: 86%
“…Föhr et al ( 24 ) investigated the association between physical activity, HRV and subjective stress measured with the perceived stress scale (PSS), finding significant changes between physical activity and HRV with stress. However, using ecological momentary assessments, Martinez et al ( 25 ) found a significant but small relationship between HRV and stress, where only a small amount of variance was explained by models. The author’s concluded that HRV might be a good proxy for stress in controlled settings with specific stressors applied, but not in real-life.…”
Section: Related Workmentioning
confidence: 99%
“…Our study, with its in the wild design, is closer to the in situ study of information workers reported by Martinez et al [26]. In that study, Martinez and colleagues found HRV to be a poor predictor of perceived stress.…”
supporting
confidence: 79%
“…During the ongoing COVID-19 pandemic, several fitness apps that have measured heart rate and HRV for exercise fitness tracking and recovery [24] have expanded to also include corporate stress and wellness monitoring. However only a handful have utilized HRV as a biomarker for stress detection and or monitoring [25]. An exploration of the literature makes it known that there are several published studies using HRV to evaluate occupational stress [26].…”
Section: Literature Reviewmentioning
confidence: 99%